Ethics in Practice and Ethnography: Faux pas During Fieldwork with Structurally Vulnerable Groups - Luxardo, Natalia (2022)
Ethical issues are an essential part of research and need to be considered throughout the process and in its aftermath, especially when including vulnerable groups. This Field Notes revisits some ethical tensions that emerged during fieldwork with a ‘vulnerable population’—a group of waste-pickers and their families—and links these to specific avenues for further thinking within ethical frameworks. I reflect on mistakes, omissions, and blunders committed over 5 years working with this social group affected by many different forms of injustices, part of my 25 years of wider research into social inequalities and health disparities within marginalised communities. I remark upon three emerging ethical tensionsrelating to: the exclusion of certain narratives; the layers of vulnerabilities and danger of harm; and the risk of stereotyping vulnerable groups. I conclude that, more than just considering ethical issues within the context of our own work as researchers on moral solipsism, decisions in applied ethics must be integrated into broader models that offer a connected rationale for the infinite situations that can emerge from research. Alternative ethical models—such as anti-racist, feminist, communitarian, and transformative approaches—provide chances for collective decision making and promote social justice, equity, and democracy.